The effect of community environment on the trajectory of depressive symptoms and cohort differences among middle-aged and older Chinese adults - Li, Xuyang (Frontiers in Public Health, 2024)
Urbanization has changed the living environment of middle-aged and elderly Chinese, but it also brings certain mental pressure to them. Few studies have explored the effect of community environment on the development trajectory and the cohort differences of depressive symptoms in Chinese individuals. Based on the longitudinal data of the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2020, using three-level hierarchical linear growth model, this study examined the effect of community environment on the trajectory of depressive symptoms and cohort differences among middle-